HUBUNGAN MEKANISME KOPING DENGAN RESIKO TERJADINYA DEPRESI PADA KORBAN PASCA BENCANA KEBAKARAN TOKO DI PASAR ATAS KOTA BUKITTINGGI TAHUN 2018 - Falerisiska Yunere; Yuli Permata Sari; Halimah Tusadiah (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
From the Word Health Organization data (WHO, 2016) shows that the number of people with mental disorders in Indonesia at this time is reaching about 236 million people with the category of mild mental disorder 6% of the population and 0.17% suffer from severe mental disorders, 14.3% experiencing disruption of the stove. 60 million people are exposed to bipolar, and 47.5 million people are affected by dementia and the incidence of depression is quite high almost more than 350 million people of the world suffer from depression and is a disease with the 4th rank in the world.The purpose of this study is to know how the Relationship Mechanism Koping With Risk of Depression in the Post Disaster Fire Disaster in pasar atas kota Bukittinggi Year 2018. This research method using descriptive analytic method with cross sectional design approach, then data processed by using Chi Square test. The sample in this research is 123 respondents. Based on the result of the research, it was found that more than half (64) 52,0% of post-disaster victims of shop fire in the city of Bukittinggi using mammaptif coping mechanism, and from the research also got result that more than half of 87 (70,0%) people are at risk of depression.The result of statistic test is obtained p value of valeu = 0,004 and OR= 0,282 (p <α) that there is a Relationship Mechanism Koping With Risk of Depression in Post Disaster Fire Disaster in pasar atas kotaBukittinggi Year 2018. So in this study can be concluded that there is a relationship between coping mechanism with the risk of depression. From this research is suggested for further researcher to know about the factors related to coping mechanism with risk of depression with more population.